2014
DOI: 10.2169/internalmedicine.53.2616
|View full text |Cite
|
Sign up to set email alerts
|

A Patient with Lung Squamous Cell Carcinoma Presenting with Severe Cardiac Dysfunction Similar to Dilated Cardiomyopathy with Left Bundle Branch Block Induced by Myocardial Metastasis

Abstract: A patient with severe cardiac dysfunction similar to dilated cardiomyopathy expired because of lung squamous cell carcinoma. He was admitted with respiratory failure and was diagnosed with congestive heart failure due to dilated cardiomyopathy based on the chest X-ray, electrocardiography, echocardiography, and coronary angiography. Chest computed tomography showed a mass shadow in the right lower lobe, and the patient was diagnosed with lung squamous cell carcinoma by bronchoscopy. The patient expired, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…retinol metabolism, arachidonic acid metabolism, linoleic acid metabolism and metabolism of xenobiotics by cytochrome p450). A report verified that it was similar in patients between with lung squamous cell carcinoma and dilated cardiomyopathy induced by myocardial metastasis (30). Besides, immunodeficiency and other immune reactions were critical in the occurrence and devel-opment of tumors.…”
Section: Discussionmentioning
confidence: 78%
“…retinol metabolism, arachidonic acid metabolism, linoleic acid metabolism and metabolism of xenobiotics by cytochrome p450). A report verified that it was similar in patients between with lung squamous cell carcinoma and dilated cardiomyopathy induced by myocardial metastasis (30). Besides, immunodeficiency and other immune reactions were critical in the occurrence and devel-opment of tumors.…”
Section: Discussionmentioning
confidence: 78%
“…As a result, we found that different gene essentiality scores have different preferences for terms without loss of plausibility. For example, there was a patient reported as LUSC with severe cardiac dysfunction similar to dilated cardiomyopathy (16) which was successfully identified by WEAT using the phastCons score. Similarly, a case with lung cancer was found to be related to the dilated phase of hypertrophic cardiomyopathy (17) which was identified by WEAT using the gene importance calculator (GIC) score.…”
Section: Resultsmentioning
confidence: 99%
“…Peluso et al noted a case of non-small cell lung cancer infiltrating the left ventricular apex and manifesting as atrial fibrillation [4]. Moreover at least two instances of ventricle myocardial metastases from primary lung cancer have been reported: Kinoshita et al reported squamous cell lung cancer leading to ventricular tachycardia secondary to right ventricle myocardial metastases [5] while Ogino et al described squamous cell cancer leading to new LBBB with myocardial metastases on autopsy [6]. Unlike benign non-infiltrating tumors which cause arrhythmia by mechanical stretching of myocardial fibers, invasive tumors can cause intramyocardial metastases which can alter the conduction pathways and trigger automaticity.…”
Section: Discussionmentioning
confidence: 99%